Grammaticality judgement in Broca's Aphasia: two case studies - Flanderková, Eva; Mertins, Barbara; Bezdíček, Ondřej; Cironisová, Eva; Černá, Marie (Česká a Slovenská neurologie a neurochirurgie, 2014)
This study presents a linguistic experiment, testing grammaticality judgment in Czech pa‑ - tients with Broca aphasia. The aim was to verify whether patients with this aphasia type - are able to distinguish between obligatory and optional verbal complements. The underly‑ - ing theoretical/ methodological framework used in the study is a functional‑ generative de‑ - scription of verb valency. Our paper comprises judgments of grammatical vs. agrammatical - sentential structures produced by of two aphasic patients with a slight and heavy cognitive - deficit respectively. The authors were able to draw the following conclusions: 1. If a sentence - is agrammatical due to violations of the government of the dependent arguments, both - patients show comprehension problems, whereas optional adverbial complements do not - disturb comprehension in either of the two patients. 2. A wrong government and a wrong - morphological marker were only helpful for detecting a defective syntactic structure for the - patient showing a slight cognitive deficit. 3. The patient with a heavy cognitive deficit relied - on lexical and/ or sentential semantics in his comprehension when evaluating the presented - material as correct. The results are interpreted in the framework of two widely used psycho‑ - linguistic models of language production/ comprehension
Gesehen am 11.11.2020